COMPLEMENTARY HYDROGEN-BONDING IN DIAMIDES - A STUDY ON THE INFLUENCE OF REMOTE SUBSTITUENTS USING DENSITY-FUNCTIONAL THEORY - Mcgrady, J; Mingos, D (1995)
Density functional calculations using gradient corrected functionals have been used to explore the factors which determine the strength of the intermolecular interaction in cyclic systems formed by complementary hydrogen bonding between amides. Optimised structures and interaction energies are presented for the simplest amide dimer, diformamide, and the results are compared with experimental and ab initio results available in the literature. Full optimisations are also performed on hydrogen bonded molecular pairs formed from the N-substituted derivatives of formamide, N-methylformamide (NMF) and N-formylformamide (NFF). The total interaction energy is found to decrease in the order NMF·NMF > NFF·NMF > NFF·NFF, the difference between successive pairs being approximately 10 kJ mol-1 in each case. The origin of this trend is traced to electrostatic repulsions between the spectator carbonyl groups in NFF and the carbonyl groups involved in the cyclic hydrogen bonded array.